Fruit Drink Consumption Is Associated With Overweight and Obesity in Canadian Women - Nikpartow, Nooshin (Can J Public Health, 2012)
OBJECTIVE: Overweight and obesity in Canada have significantly increased during the last three decades, paralleled by increased intake of fat and sugar, particularly sugary beverages. The Canadian Community Health Survey, Cycle 2.2, conducted in 2004 (CCHS 2.2), provides the opportunity to evaluate beverage intakes in relation to overweight and obesity using body mass index (BMI). Our objective was to examine the association between sugar-sweetened beverages and BMI in Canadian adults. METHODS: CCHS 2.2 data were used (n=14,304, aged >18 years and <-65 years) and dietary intake was assessed on the basis of single 24-hour recall. Using cluster analysis (K-means method), males and females were classified into distinct clusters based on the dominant pattern of beverage intakes. Logistic regression models were used to determine associations between dominant beverage consumption patterns and BMI, controlling for age and other confounding factors. RESULTS: BMI in women with predominant “fruit drink” pattern (28.3 ± 1.0 kg/m(2)) was higher than in those with no dominant pattern (26.8 ±0.3 kg/m(2)), p<0.001. Adjusting for energy intake and other potential confounders, high intake of fruit drinks was a significant predictor of overweight (OR=1.84, 95% CI: 1.06-3.20), obesity (OR=2.55, 95% CI: 1.46-4.47) and overweight/obesity (OR=2.05, 95% CI: 1.29-3.25) in women. In men, mean BMI was not different among beverage consumption clusters and none of the beverage intake patterns was a predictor for overweight and obesity. CONCLUSION: Using a nationally representative dataset, there was an association between sugar-sweetened beverages and overweight and obesity in Canadian women.